2013
DOI: 10.3149/fth.1102.118
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Mothers' and Fathers' Initial Fathering Identities and Later Father-Child Relationship Quality

Abstract: Children benefit from high quality relationships with their fathers in a number of ways. However, little is known about the origins of father-child relationships. Here, identity theory and data from the Fragile Families dataset are used to investigate associations between mothers' and fathers' fathering identities at the time of the child's birth and nine years later, and the father-child relationship as reported by children at age nine. Neither mothers' nor fathers' role identity standards at birth were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
(74 reference statements)
1
22
0
1
Order By: Relevance
“…Adamsons () used Fragile Families and Child Wellbeing (FFCW) data to create a measure consistent with FCRQ constructs. Specifically, at year 9, children were interviewed and child reports of FCRQ were used.…”
Section: Methodological Challenges and Advances In Studying Fcrqmentioning
confidence: 99%
See 1 more Smart Citation
“…Adamsons () used Fragile Families and Child Wellbeing (FFCW) data to create a measure consistent with FCRQ constructs. Specifically, at year 9, children were interviewed and child reports of FCRQ were used.…”
Section: Methodological Challenges and Advances In Studying Fcrqmentioning
confidence: 99%
“…Along this line of reasoning, Adamsons () has recently observed that it has been “well established that positive fathering behaviors have extensive benefits for children (Lamb, ). However, more research has been conducted regarding the outcomes resulting from various forms of father involvement (Hofferth, Pleck, Stueve, Bianchi, & Sayer, ; Marsiglio, Amato, Day, & Lamb, ; Marsiglio & Cohan, ; Pleck, ) than benefits or predictors of relationships between fathers and their children.” (p. 118, emphasis in original)…”
Section: Moving Beyond Mere Frequenciesmentioning
confidence: 99%
“…In fact, we believe that few studies have examined what seems to matter most for children: the quality of father involvement (e.g., warmth, responsiveness; Carlson, ; Pleck, ) and financial provisions (particularly for nonresident and unmarried fathers, which may include informal contributions common among unmarried fathers; Amato & Gilbreth, ). A few notable exceptions include Adamsons (; closeness), DeGarmo (; positive involvement), Fox and Bruce (; harshness), and Habib and Lancaster (, ; antenatal attachment quality).…”
Section: A Few Final Observationsmentioning
confidence: 99%
“…In 19 of the studies, identity salience and/or centrality were measured at the status level (e.g., Bruce & Fox, 1999;Henley & Pasley, 2005); six also included measures at the role level (e.g., Habib & Lancaster, 2006;Maurer, 2007;Rane & McBride, 2000); and two studies (Maurer et al, 2001;Maurer & Pleck, 2006) addressed only role-level identity. Further, two studies included specific assessments of only salience (Bruce & Fox, 1999;DeGarmo & Forgatch, 2002), five of only centrality (e.g., Adamsons & Pasley, 2013;Habib & Lancaster, 2006), and six with both salience and centrality (e.g., Adamsons, 2013;Rane & McBride, 2000). Three studies include identity commitment, typically measured as reflected appraisals or perceived reflected appraisals (e.g., Maurer et al, 2001), of which two included salience (Henley & Pasley, 2005;Pasley et al, 2002) and five included centrality (e.g., Maurer, 2007;Maurer & Pleck, 2006;McBride & Rane, 1997).…”
Section: Primary Findings: Linking Identity Salience and Centrality Wmentioning
confidence: 99%
“…I identified five papers that used identity theory based on FFCW data (Adamsons, 2013;Castillo et al, 2011;Guzzo, 2009;Karen, 2009;Hohmann-Marriott, 2009). Parental identity has been defined as the degree to which an individual views parenting domains (e.g., caregiving) as important to one's self (Maurer, Pleck, & Rane, 2001).…”
Section: Identity Theorymentioning
confidence: 99%